Imaging Intraplaque Inflammation in Carotid Atherosclerosis With 18F-Fluorocholine Positron Emission Tomography–Computed Tomography: Prospective Study on Vulnerable Atheroma With Immunohistochemical Validation. (May 2016) - Vöö, Stefan; Kwee, Robert M.; Sluimer, Judith C.; Schreuder, Floris H. B. M.; Wierts, Roel; Bauwens, Matthias; Heeneman, Sylvia; Cleutjens, Jack P. M.; van Oostenbrugge, Robert J.; Daemen, Jan-Willem H.; Daemen, Mat J. A. P.; Mottaghy, Felix M.; et al.
Abstract : Background—: 18 F-fluorocholine ( 18 F-FCH) uptake is associated with cell proliferation and activity in tumor patients. We hypothesized that 18 F-FCH could similarly be a valuable imaging tool to identify vulnerable plaques and associated intraplaque inflammation and atheroma cell proliferation. Methods and Results—: Ten consecutive stroke patients (90% men, median age 66.5 years, range, 59.4–69.7) with ipsilateral >70% carotid artery stenosis and who underwent carotid endarterectomy were included in the study. Before carotid endarterectomy, all patients underwent positron emission tomography to assess maximum 18 F-FCH uptake in ipsilateral symptomatic carotid plaques and contralateral asymptomatic carotid arteries, which was corrected for background activity, resulting in a maximum target-to-background ratio (TBRmax). Macrophage content was assessed in all carotid endarterectomy specimens as a percentage of CD68 + -staining per whole plaque area (plaqueCD68 + ) and as a maximum CD68 + percentage (maxCD68 + ) in the most inflamed section/plaque. Dynamic positron emission tomography imaging demonstrated that an interval of 10 minutes between 18 F-FCH injection and positron emission tomography acquisition is appropriate for carotid plaque imaging. TBRmax in ipsilateral symptomatic carotid plaques correlated significantly with plaqueCD68 + (Spearman's ρ=0.648, P =0.043) and maxCD68 + (ρ=0.721, P =0.019) in the 10 corresponding carotid endarterectomy specimens. TBRmax was significantly higher ( P =0.047) in ipsilateral symptomatic carotid plaques (median: 2.0; interquartile range [Q1–Q3], 1.5–2.5) compared with the contralateral asymptomatic carotid arteries (median: 1.4; Q1–Q3, 1.3–1.6). TBRmax was not significantly correlated to carotid artery stenosis (ρ=0.506, P =0.135). Conclusions—: In vivo uptake of 18 F-FCH in human carotid atherosclerotic plaques correlated strongly with degree of macrophage infiltration and recent symptoms, thus 18 F-FCH positron emission tomography is a promising tool for the evaluation of vulnerable plaques. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01899014. Abstract : Supplemental Digital Content is available in the text.